The Effects of Incremental Doses of Aflatoxin B1 on In Vitro Ruminal Nutrient Digestibility and Fermentation Profile of a Lactating Dairy Cow Diet in a Dual-Flow Continuous Culture System - Amaro, Felipe Xavier; Jiang, Yun; Arriola, Kathy; Pupo, Matheus R.; Agustinho, Bruna C.; Bennett, Sarah L.; Vinyard, James R.; Tomaz, Lais [UNESP]; Lobo, Richard R.; Pech-Cervantes, Andres; Arce-Cordero, Jose A.; Faciola, Antonio P.; et al. (MDPI, 2023)
Aflatoxin B1 (AFB1) is a mycotoxin known to impair human and animal health. It is also believed to have a deleterious effect on ruminal nutrient digestibility under in vitro batch culture systems. The objective of this study was to evaluate the effects of increasing the dose of AFB1 on ruminal dry matter and nutrient digestibility, fermentation profile, and N flows using a dual-flow continuous culture system fed a diet formulated for lactating dairy cows. Eight fermenter vessels were used in a replicated 4 × 4 Latin square design with 10 d periods (7 d adaptation and 3 d sample collection). Treatments were randomly applied to fermenters on diet DM basis: (1) 0 μg of AFB1/kg of DM (Control); (2) 50 μg of AFB1/kg of DM (AF50); (3) 100 μg of AFB1/kg of DM (AF100); and (4) 150 μg of AFB1/kg of DM (AF150). Treatments did not affect nutrient digestibility, fermentation, and N flows. Aflatoxin B1 concentration in ruminal fluid increased with dose but decreased to undetectable levels after 4 h post-dosing. In conclusion, adding incremental doses of AFB1 did not affect ruminal fermentation, digestibility of nutrients, and N flows in a dual-flow continuous culture system fed diets formulated for lactating dairy cows.
Keywords: aflatoxin B1; mycotoxin; N metabolism; nutrient digestibility; rumen fermentation; ruminal microbial protein